PREVALENCE OF HYPERURICEMIA AMONG PATIENTS WITH METABOLIC SYNDROME: RESULTS OF THE STUDY IN REAL CLINICAL PRACTICE - D. V. Nebieridze; N. V. Dolgushina (Столичная издательская компания, 2017)
Interview of Professor D.V. Nebieridze